Pleural tuberculosis: medical thoracoscopy greatly increases the diagnostic accuracy. Issue 1 (5th January 2018) - Casalini, Angelo Gianni; Mori, Pier Anselmo; Majori, Maria; Anghinolfi, Miriam; Silini, Enrico Maria; Gnetti, Letizia; Motta, Federica; Larini, Sandra; Montecchini, Sara; Pisi, Roberta; Calderaro, Adriana
Our objective was to evaluate the efficacy of a standardised work-up in the diagnosis of pleural tuberculosis (TB) that included fibreoptic bronchoscopy and medical thoracoscopy. A consecutive series of 52 pleural TB patients observed during the period 2001–2015 was evaluated retrospectively. 20 females, mean (range) age 39.7 (18–74) years, and 32 males, mean (range) age 45.75 (21–83) years, were included (28 non-EU citizens (53.8%)). The diagnosis of TB infections was established by identification (using stains, culture or molecular tests) of Mycobacterium tuberculosis in the pleura, sputum and/or bronchial specimens, or by evidence of caseous granulomas on pleural biopsies. Patients with and without lung lesions were considered separately. The diagnostic yield of the microbiological tests on pleural fluid was 17.3% (nine out of 52 patients). Among the 18 patients with lung lesions, bronchial samples (washing, lavage or biopsy) were positive in 50% of cases (nine patients). Cultures of pleural biopsies were positive in 63% of cases (29 out of 46 patients); pleural histology was relevant in all patients. Without pleural biopsy, a diagnosis would have been reached in 15 out of 52 patients (28.6%) and in four of them only following culture at 30–40 days. An integrated diagnostic work-up that includes all the diagnostic methods of interventional pulmonology is required for a diagnosis of pleural TB. In the majority of patients, a diagnosis can be reached only with pleural biopsy. Diagnosis of tuberculous pleural effusion can be a challenge; medical thoracoscopy greatly increases accuracy http://ow.ly/EnY430gubm9